Physical demands at work, physical fitness, and 30-year ischaemic heart disease and all-cause mortality in the Copenhagen Male Study - Andreas Holtermann (Scandinavian Journal of Work, Environment & Health, 2010)

(untitled)
OBJECTIVE: No previous long-term prospective studies have examined if workers with low cardiorespiratory fitness have an increased risk of cardiovascular mortality due to high physical work demands. We tested this hypothesis. METHOD: We carried out a 30-year follow-up of the Copenhagen Male Study of 5249 employed men aged 40–59 years. We excluded from follow-up 274 men with a history of myocardial infarction, prevalent symptoms of angina pectoris, or intermittent claudication. We estimated physical fitness [maximal oxygen consumption (VO_2Max)] using the Åstrand cycling test and determined physical work demands with two self-reported questions. RESULTS: In the Copenhagen Male Study, 587 men (11.9%) died due to ischaemic heart disease (IHD). Using men with low physical work demands as the reference group, Cox analyses – adjusted for age, blood pressure, smoking, alcohol consumption, body mass index, diabetes, and hypertension – showed that high physical work demands were associated with an increased risk of IHD mortality in the least fit [VO_2Max range 15–26, N=892, hazard ratio (HR) 2.04, 95% confidence interval (95% CI) 1.20–3.49] and moderately fit (VO_2Max range 27–38, N=3037, HR 1.75, 95% CI 1.24–2.46), but not among the most fit men (VO_2Max range 39–78, N=1014, HR 1.08, 95% CI 0.52–2.17). We found a similar, although slightly weaker, relationship with respect to all-cause mortality. CONCLUSIONS: The hypothesis was supported. Men with low and medium physical fitness have an increased risk of cardiovascular and all-cause mortality if exposed to high physical work demands. Ours observations suggest that, among men with high physical work demands, being physically fit protects against adverse cardiovascular effects.